2014
DOI: 10.3136/fstr.20.765
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chlorine-Based Antimicrobial Treatments on the Microbiological Qualities of Selected Leafy Vegetables and Wash Water

Abstract: The disinfection efficacy of sodium hypochlorite (NaClO) and chlorine dioxide (ClO 2 ) was evaluated singly or in combination with micro-bubbling, ultra-sonication, or mild heat (50℃) against microorganisms on lettuce, spinach and Chinese cabbage. There were no significant differences in reductions of either intrinsic microflora or inoculated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…Zhang and Farber [48] reported the maximum log 10 reduction of L. monocytogenes at 4 and 22° C to be 1.3 and 1.7 log 10 CFU/g for lettuce and 0.9 and 1.2 log 10 CFU/g for cabbage, respectively. In the current study, chlorine (200 ppm) produced greater reductions for inoculated pathogens versus naturally occurring Enterobacteriaceae (Table 1 and Table 2; Figure 1), similar to results reported by other researchers testing 100–200 ppm HOCl on spinach [49,50], potentially resulting from differences in differing attachment strengths from naturally occurring versus inoculated pathogen cells, as well as potential for naturally occurring cells to locate effectively into protected niches on the leaf surface [51]. Erkman [52] reported that 10 ppm HOCl (pH 7.0) applied via immersion with agitation for 5 min reduced E. coli on lettuce, parsley, and pepper by 1.2, 1.6, and 2.6 log 10 CFU/mL, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…Zhang and Farber [48] reported the maximum log 10 reduction of L. monocytogenes at 4 and 22° C to be 1.3 and 1.7 log 10 CFU/g for lettuce and 0.9 and 1.2 log 10 CFU/g for cabbage, respectively. In the current study, chlorine (200 ppm) produced greater reductions for inoculated pathogens versus naturally occurring Enterobacteriaceae (Table 1 and Table 2; Figure 1), similar to results reported by other researchers testing 100–200 ppm HOCl on spinach [49,50], potentially resulting from differences in differing attachment strengths from naturally occurring versus inoculated pathogen cells, as well as potential for naturally occurring cells to locate effectively into protected niches on the leaf surface [51]. Erkman [52] reported that 10 ppm HOCl (pH 7.0) applied via immersion with agitation for 5 min reduced E. coli on lettuce, parsley, and pepper by 1.2, 1.6, and 2.6 log 10 CFU/mL, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…A reduction of <1 log CFU•g −1 after a 5 min dip in 100 mg•L −1 free chlorine compared to a plain water dip when inoculated lettuce leaves with E. coli was obtained by Behrsing et al [34]. Pan and Nakano [35] also observed a reduction of approximately 2 log CFU/g in E. coli O157:H7 levels on leafy vegetables, as lettuce was washed with NaClO at 0, 50, 100, 200, and 500 ppm for 5 min compared with the unwashed lettuce. Seo and Frank [36] showed that while E. coli O157:H7 cells on the surface of iceberg lettuce leaves were killed by a 20 mg•L −1 chlorine decontamination treatment, the cells inside the stomata or those which had penetrated the cut edge of a leaf survived.…”
Section: Resultsmentioning
confidence: 91%
“…However, chemical agents are often less efficient than physical methods (e.g., heat and pressure) in achieving microbial reduction. This limitation is, in part, due to regulatory limits on the allowable concentrations of these chemical agents in food and water systems and to the dependence of their biological activity on factors such as pH and temperature (10,11). Consequently, extended exposure times are often required to achieve an effective microbial load reduction using chemical agents.…”
mentioning
confidence: 99%
“…Consequently, extended exposure times are often required to achieve an effective microbial load reduction using chemical agents. To overcome these limitations, traditionally some chemical agents have been used following an initial physical treatment, mainly with the aims of extending the shelf life of food and preserving food and water systems (10,12).…”
mentioning
confidence: 99%
See 1 more Smart Citation